Fabrication and assessment of potent anticancer nanoconjugates from chitosan nanoparticles, curcumin, and eugenol - El-Sherbiny, Mohsen M.; Elekhtiar, Rawan S.; El-Hefnawy, Mohamed E.; Mahrous, Hoda; Alhayyani, Sultan; Al-Goul, Soha T.; Orif, Mohamed I.; Tayel, Ahmed A. (Frontiers in Bioengineering and Biotechnology, 2022)
In cancer’s management and control, from the most challenging difficulties are the complications resulted from accustomed therapies. The constitution of bioactive anticancer nanoconjugates from natural derivatives, e.g. chitosan (Ct), curcumin (Cur) and eugenol (Eug), was investigated, as potential alternatives for cancer cells’ treatment. The Ct was extracted from Erugosquilla massavensis (mantis shrimp); then Ct nanoparticles (NCt) was fabricated and loaded with Cur and/or Eug using crosslinking emulsion/ionic-gelation protocol, and then evaluated as anticancer composites against CaCo2 “colorectal adenocarcinoma” and MCF7 “breast adenocarcinoma” cells. Ct had 42.6 kDa molecular weight and 90.7 % deacetylation percentage. The conjugation of fabricated molecules/composites and their interactions were validated via infra-red analysis. The generated nanoparticles (NCt, NCt/Cur, NCt/Eug and NCt/Cur/Eug composites) had mean particles’ size diameters of 268.5, 314.9, 296.4 and 364.7 nm, respectively; the entire nanoparticles carried positive charges nearby ≥ 30 mV. The scanning imaging of synthesized nanoconjugates (NCt/Cur, NCt/Eug and NCt/Cur/Eug) emphasized their homogenous distributions and spherical shapes. The cytotoxic assessments of composited nanoconjugates using MTT assay, toward CaCo2 and MCF7 cells, revealed elevated anti-proliferative and dose-dependent activities of all nanocomposites against treated cells. The combined nanocomposites (NCt/Eug/Cur) emphasized the highest activity against CaCo2 cells (IC50=11.13 µg/mL), followed by Cur/Eug then NCt/Cur. The exposure of CaCo2 cells to the nanocomposites exhibited serious DNA damages and fragmentation in exposed cancerous cells, using comet assay; the NCt/Eug/Cur nanocomposite was the most forceful with 9.54 nm tail length and 77.94 tail moment. The anticancer effectuality of innovatively combined NCt/Cur/Eug nanocomposite is greatly recommended using such biosafe, natural, biocompatible and powerful anticancer materials, especially for combating colorectal adenocarcinoma cells, with elevated applicability, efficiency and biosafety.